2020
DOI: 10.3390/ijerph17217871
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Exposure of Reproductive-Age Farmworkers in Chiang Mai Province, Thailand, to Organophosphate and Neonicotinoid Insecticides: A Pilot Study

Abstract: Exposure to insecticides containing organophosphate (OP) and neonicotinoid (NEO) compounds has been associated with adverse reproductive health outcomes. This study characterized and identified predictors of exposure to OP and NEO among 100 reproductive-age farmworkers from two intensive farming areas in Chiang Mai Province, Thailand, including 50 each from the Fang (FA) and Chom Thong (CT) districts. OP exposure was determined by measuring the urinary concentrations of six dialkylphosphates (DAPs), whereas NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 53 publications
1
14
1
Order By: Relevance
“…The structured questionnaire was modified from the pilot study [ 31 ]. Reliability and validity were tested as quality control (QC) of the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The structured questionnaire was modified from the pilot study [ 31 ]. Reliability and validity were tested as quality control (QC) of the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Urinary OP metabolites including dimethylphosphate (DMP), dimethylthiophosphate (DMTP), diethylphosphate (DEP), diethylthiophosphate (DETP) and diethyldithiophosphate (DEDTP) were measured by gas chromatography with a flame photometric detector according to the previously established method using an Agilent 7890-B GC system (Agilent Technologies, Inc., Santa Clara, CA, USA) [ 34 ]. The procedure was briefly described in our previous study [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, increasing numbers of epidemiological studies have demonstrated the impacts of OPPs on neurodevelopment in children [ 3 , 4 , 5 ] and via prenatal exposure [ 6 ]. Some studies reported that human exposure to OPPs is associated with the season; intake of certain food items, such as vegetables (tomato and sweet pepper), fruits (apple, banana, citrus, kiwi and apricot), beans, bread and drinking water; and the use of pesticides in workplaces [ 7 , 8 , 9 ]. Similar results were obtained from large-scale birth cohort studies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%